The Role of Facilitation in Technology-Enhanced Learning for Public Employment Services - Bimrose, Jenny; Brown, Alan; Holocher-Ertl, Teresa; Kieslinger, Barbara; Kunzmann, Christine; Prilla, Michael; Schmidt, Andreas; Wolf, Carmen (International Journal of Advanced Corporate Learning (iJAC), 2014)
Public Employment Services (PES) in Europe are authorities that attempt to match supply and demand on the labor market. Rising unemployment in times of crisis and demographic change are among the main challenges with which PES practitioners, as a direct interface between jobseekers and employers, have to deal. They have to support career adaptability of their clients as well as to enhance and transform their own individual and collective professional identities in order to cope successfully with the challenges of a changing labor market. As part of the research project EmployID, we are exploring how to facilitate the learning process of PES practitioners in their professional identity development. The aim of the project is to empower individual PES practitioners, their community and organizations, to engage in transformative practices, using a holistic tool suite combining e-coaching, reflection, MOOCs, networking, analytical and learning support tools. Key to successful professional identity transformation is continuous learning. Individuals may take on the role of facilitators for the learning of others as well as being facilitated by peers, technology and environment.